2016
DOI: 10.1186/s12885-016-2219-z
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophil-to-lymphocyte ratio is a prognostic marker in bladder cancer patients after radical cystectomy

Abstract: BackgroundThere is no reliable biomarker for predicting the prognosis of patients who undergo radical cystectomy for bladder cancer. Recent studies have shown that the neutrophil-to-lymphocyte ratio (NLR) could function as a useful prognostic factor in several types of malignancies. This study aimed to assess the usefulness of NLR in bladder cancer.MethodsA total of 74 patients who underwent radical cystectomy in our institutions from 1999 to 2014 were analyzed. The NLR was calculated using the patients’ neutr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
33
2

Year Published

2016
2016
2018
2018

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 49 publications
(35 citation statements)
references
References 43 publications
(51 reference statements)
0
33
2
Order By: Relevance
“…Some of these studies revealed correlations between NLR and prognosis of patients with UUT-UC who underwent nephroureterectomy [17][18][19][20]. In urothelial carcinoma, our previous reports showed the cut-off points as 2.38 for the patients who received radical cystectomy and the other reports in bladder cancer showed similar cut-off point (2.38 -3.0) [11]. For UUT-UC, the cut-off points were 2.5 to 2.7 [19,20].…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…Some of these studies revealed correlations between NLR and prognosis of patients with UUT-UC who underwent nephroureterectomy [17][18][19][20]. In urothelial carcinoma, our previous reports showed the cut-off points as 2.38 for the patients who received radical cystectomy and the other reports in bladder cancer showed similar cut-off point (2.38 -3.0) [11]. For UUT-UC, the cut-off points were 2.5 to 2.7 [19,20].…”
Section: Discussionmentioning
confidence: 83%
“…In particular, C-reactive protein as a systemic inflammation marker was reported to be a poor prognostic factor in several types of cancers [6,7]. Others and we have also revealed that neutrophil-to-lymphocyte ratio (NLR) is an independent prognostic factor in various solid malignancies, including renal cell carcinoma, bladder urothelial carcinoma, and prostatic carcinoma [8][9][10][11][12][13]. Of note, NLR can be easily calculated from complete blood counts (CBCs) in the peripheral blood, and this parameter can be used both pre-and post-operatively.…”
Section: Introductionmentioning
confidence: 96%
“…CBCs are typically examined during the clinical check-up, and the NLR can be applied to all patients virtually either before or after surgery/medical treatment. We previously reported NLR as an independent prognosticator in men presenting with metastatic prostate cancer as well as in bladder cancer patients who received radical cystectomy [14]. Indeed, NLR has been shown to be a prognostic factor in patients with bladder cancer [12, 1519].…”
Section: Discussionmentioning
confidence: 99%
“…We previously assessed the utility of NLR as a biomarker to predict tumor recurrence and cancer death in bladder cancer patients who underwent radical cystectomy [14]. In the current study, we investigated whether NLR could predict the prognosis of bladder cancer patients who received gemcitabine and nedaplatin (GN) chemotherapy.…”
Section: Introductionmentioning
confidence: 99%
“…[23,24] Kawahara et al [25] showed that the NLR was an independent prognostic factor in bladder cancer patients who underwent RC. Potretzke et al [11] demonstrated that patients with preoperative NLR elevation could be upstaged at the time of RC and might benefit from neo-adjuvant chemotherapy.…”
Section: Discussionmentioning
confidence: 99%